It is currently 14 Dec 2018, 01:44
My Tests

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

If L = (a - b)-c and R =a - (b - c), then L - R =

  Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:
Moderator
Moderator
User avatar
Joined: 18 Apr 2015
Posts: 5166
Followers: 77

Kudos [?]: 1033 [0], given: 4655

CAT Tests
If L = (a - b)-c and R =a - (b - c), then L - R = [#permalink] New post 04 Aug 2018, 10:43
Expert's post
00:00

Question Stats:

62% (00:36) correct 37% (00:48) wrong based on 8 sessions
If \(L = (a - b)- c\) and \(R = a - (b - c)\), then \(L - R =\)

(A) 2b

(B) 2c

(C) 0

(D) -2b

(E) -2c
[Reveal] Spoiler: OA

_________________

Get the 2 FREE GREPrepclub Tests

1 KUDOS received
GRE Instructor
User avatar
Joined: 10 Apr 2015
Posts: 1238
Followers: 46

Kudos [?]: 1126 [1] , given: 7

Re: If L = (a - b)-c and R =a - (b - c), then L - R = [#permalink] New post 04 Aug 2018, 17:11
1
This post received
KUDOS
Expert's post
Carcass wrote:
If \(L = (a - b)- c\) and \(R = a - (b - c)\), then \(L - R =\)

(A) 2b

(B) 2c

(C) 0

(D) -2b

(E) -2c


Given: L = (a - b)- c
Simplify to get: L = a - b - c

Given: R = a - (b - c)
R = a - b + c

So, L - R = (a - b - c) - (a - b + c)
= a - b - c - a + b - c
= -2c

Answer: E

Cheers,
Brent
_________________

Brent Hanneson – Creator of greenlighttestprep.com
Image
Sign up for our free GRE Question of the Day emails

Re: If L = (a - b)-c and R =a - (b - c), then L - R =   [#permalink] 04 Aug 2018, 17:11
Display posts from previous: Sort by

If L = (a - b)-c and R =a - (b - c), then L - R =

  Question banks Downloads My Bookmarks Reviews Important topics  


cron

GRE Prep Club Forum Home| About| Terms and Conditions and Privacy Policy| GRE Prep Club Rules| Contact

Powered by phpBB © phpBB Group

Kindly note that the GRE® test is a registered trademark of the Educational Testing Service®, and this site has neither been reviewed nor endorsed by ETS®.